Does environmental regulation drive or hinder the development of new quality productive forces? evidence from Chinese listed firms - Chen, Qi; Su, Huaqiang; Gao, Weixin; Lv, Jingjing (Frontiers in Environmental Science, 2025)
Introduction:This study investigates the nonlinear dynamics between environmental regulation (ER) and the development speed of New Quality Productive Forces (NQPF) by integrating compliance cost effects and innovation compensation effects into a unified framework.Introduction:Using panel data from Chinese A-share listed firms (2012–2022), we apply fixed-effects model and nonlinear mediation analysis (via the SPSS Medcurve program) to quantify the inverted U-shaped ER-NQPF relationship, incorporating robustness checks for endogeneity and heterogeneity across industries, regions, and ownership types.Results and Discussion:We identify a robust inverted U-shaped relationship, with moderate ER intensity stimulating productivity gains through innovation incentives, while excessive stringency suppresses growth due to escalating compliance costs. Mechanism analyses reveal that compliance costs mediate this relationship nonlinearly, whereas innovation investment—particularly R&D expenditures—exerts a negative mediating effect, reflecting resource diversion toward short-term compliance over transformative innovation. Heterogeneity tests underscore critical disparities across industries, regions, and firm ownerships, challenging the universality of the Porter Hypothesis in transitional economies. Practically, the findings advocate for spatially and sectorally differentiated environmental policies, emphasizing institutional readiness and localized innovation ecosystems. This study redefines the ER-productivity debate by integrating institutional context and firm-level adaptability, offering actionable insights for sustainable governance in emerging economies.